TRIQS/CTHYB: A continuous-time quantum Monte Carlo hybridisation expansion solver for quantum impurity problems - Seth, Priyanka; Krivenko, Igor; Ferrero, Michel; Parcollet, Olivier (Computer physics communications, 2016)
We present TRIQS/CTHYB, a state-of-the art open-source implementation of the continuous-time hybridisation expansion quantum impurity solver of the TRIQS package. This code is mainly designed to be used with the TRIQS library in order to solve the self-consistent quantum impurity problem in a multi-orbital dynamical mean field theory approach to strongly-correlated electrons, in particular in the context of realistic electronic structure calculations. It is implemented in C++ for efficiency and is provided with a high-level Python interface. The code ships with a new partitioning algorithm that divides the local Hilbert space without any user knowledge of the symmetries and quantum numbers of the Hamiltonian. Furthermore, we implement higher-order configuration moves and show that such moves are necessary to ensure ergodicity of the Monte Carlo in common Hamiltonians even without symmetry-breaking. Program title: TRIQS/CTHYB Catalogue identifier: AEYU_v1_0 Program summary URL:http://cpc.cs.qub.ac.uk/summaries/AEYU_v1_0.html Program obtainable from: CPC Program Library, Queen’s University, Belfast, N. Ireland. Licensing provisions: GNU General Public Licence (GPLv3) No. of lines in distributed program, including test data, etc.: 159,017 No. of bytes in distributed program, including test data, etc.: 10,215,893 Distribution format: tar.gz Programming language: C++/Python. Computer: Any architecture with suitable compilers including PCs and clusters. Operating system: Unix, Linux, OSX. RAM: Highly problem-dependent Classification: 7.3, 4.4. External routines: TRIQS, cmake. Nature of problem: Accurate solvers for quantum impurity problems are needed in condensed matter theory. Solution method: We present an efficient C++/Python open-source implementation of a continuous-time hybridisation expansion solver. Running time: Tests take less than a minute. Otherwise it is highly problem dependent (from minutes to several days).